2016
DOI: 10.1016/j.jegh.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of uninvestigated dyspepsia, irritable bowel syndrome, and gastroesophageal reflux disease among students of Damascus University, Syria

Abstract: Uninvestigated dyspepsia (UD), irritable bowel syndrome (IBS), and gastroesophageal reflux disease (GERD) are common disorders universally. Many studies have assessed their epidemiological characteristics around the world. However, such information is not known for Syria. We aim to estimate the epidemiologic characteristics and possible risk factors for UD, IBS, and GERD among students at Damascus University, Damascus, Syria. A cross-sectional study was conducted in July-September 2015 at a campus of Damascus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 21 publications
3
38
2
Order By: Relevance
“…The prevalence of IBS in the current study is in line with earlier reports from Asian countries [ 21 , 22 ]; however, it is much higher than global prevalence due to the use of a modified Rome III criteria rather than a clinical assessment for identification of IBS [ 23 ]. IBS is associated with several disabilities and significant incurred costs.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of IBS in the current study is in line with earlier reports from Asian countries [ 21 , 22 ]; however, it is much higher than global prevalence due to the use of a modified Rome III criteria rather than a clinical assessment for identification of IBS [ 23 ]. IBS is associated with several disabilities and significant incurred costs.…”
Section: Discussionsupporting
confidence: 90%
“…We found no association between smoking habits and risk of IBS, in line with a recent systematic review, but in contrast with other cross‐sectional studies . The lack of significant associations between healthy lifestyle factors, including dietary intakes, physical activity, and smoking, with IBS might be due to the use of binary variables to quantify these factors in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Up to now, results on diet-GERD relationship are inconsistent among various studies. Several studies reported that consumption of caffeinated beverages (coffee and tea), carbonated drinks, citrus fruit, chocolate, spicy foods, and large-volume meals, were related to higher risk of GERD or triggering symptoms [ 8 , 9 , 27 29 ]. It is proposed that these foods can decrease LES pressure and/or slow gastric emptying which may result in development of GERD symptoms [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in this study, the amount of the liquid intake was not recorded. Some studies have shown that intake of large volumes of liquid may be associated with GERD development or disease severity [ 8 , 28 ]. Moreover, it is proposed that this association may vary, depending on whether or not the liquid is consumed with meals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation